Green Synthesis of Nickel Aluminum Layered Double Hydroxide using Chitosan as Template for Adsorption of Phenol - Hasja Paluta Utami; Nur Ahmad; Zaqiya Artha Zahara; Aldes Lesbani; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
In present study, a modification of the NiAl LDH composite with chitosan was successful. Characterization was carried out using X-rays, The results obtained show that there is an angle of 2θ at 11.57°(003); 22.91°(006); 35.04°(012); 39.73°(015); and 61.9°(110). The FT-IR spectrum of the Chitosan@NiAl LDH at Wavenumber 3448, 1635, 1543, and 601 cm−1. The NiAl LDH and chitosan have a surface area of 3.288 m2/g and 8.558 m2/g, respectively. An increase in the surface area of the composite Chitosan@NiAl LDH 9.493 m2/g, all of adsorbents follow type IV isotherm based on the classification according to IUPAC. The optimum pH of the NiAl LDH at pH 3. The optimum pH for chitosan and chitosan@NiAl LDH material is at the optimum pH of 5. The kinetic and isotherm model in the adsorption process is pseudo-second-order and Freundlich model, respectively. The maximum adsorption capacity of NiAl LDH, chitosan, and chitosan@NiAl LDH is 25.445, 23.753, and 33.223 mg/g, respectively. The increase in regeneration cycles causes a decrease in the percentage of adsorbed; sequentially, the percentage adsorbed during the fifth regeneration reaches 3.545, 1.966, 4.309%, respectively.